Clinical value of diagnostic instruments for ruling out acute coronary syndrome in patients with chest pain: a systematic review. Issue 12 (3rd August 2010) - Steurer, Johann; Held, Ulrike; Schmid, Dominic; Ruckstuhl, Jan; Bachmann, Lucas M
Abstract : Background: Acute chest pain is a frequent reason to attend an emergency room, and various instruments for calculating the probability of an acute coronary syndrome exist. Objective: To assess the safety and efficiency of all available instruments investigated in sample validation studies. Methods: A systematic review was conducted. Studies were identified describing the development of instruments and all subsequent validations in electronic databases and reference lists of included studies. Inclusion was screened for, full papers checked and data extracted on salient clinical features, performance characteristics and quality in duplicate. Results: Of 20 derivation studies, 10 were at least validated once in 14 validations including 26 488 patients. One study by Selker and colleagues was validated in six new patient series and studies by Goldman et al and the Kennedy et al were both validated in three new patient series. All other studies were validated less than three times. In four out of six validations of the Selker et al study, the sensitivity of the prediction rule was 98% or higher. The corresponding values for specificity ranged from 4% to 34%. All remaining prediction rules showed sensitivity values below 95% in all validations. Conclusions: No instrument assisting clinicians in the diagnostic investigation of patients with suspected acute coronary syndrome consistently fulfils the safety requirements of clinicians.